The Effectiveness of the GASING Method in Improving Mathematical Procedural Understanding Ability in Multiplication Among Phase B Elementary School Students - Manda Safitri; Sandi Budi Iriawan; Rosiana Mufliva (PALAPA, 2025)
This study addresses the persistent challenge of limited procedural understanding in multiplication among elementary school students in Indonesia, particularly those in Phase B. Many students struggle to follow correct steps, select appropriate strategies, and apply multiplication concepts to real-life contexts—issues often exacerbated by traditional teaching methods that prioritize rote memorization over active, tangible learning experiences. The study aims to examine the effectiveness of the GASING method in enhancing procedural understanding of multiplication among fourth-grade students. Employing a pre-experimental one-group pre-test and post-test design, the study involved 24 purposively selected students. Data were collected using pre- and post-test instruments and analyzed through the Wilcoxon test. Results indicate a significant improvement in students' procedural understanding following the intervention, with a p-value of 0.001, demonstrating statistical significance at the 0.05 level. The findings affirm that the GASING method—characterized by its concrete, visual, and interactive learning approach—effectively strengthens students’ procedural skills in mathematics. This research contributes to the growing literature on innovative teaching methods in mathematics education and provides practical guidance for educators seeking to implement engaging, structured instructional strategies.